Empire forestry and the origins of environmentalism - Barton, Greg (Gregory Allen) (Cambridge studies in historical geography, 2002)
What we now know of as environmentalism began with the establishment of the first empire forest in 1855 in British India. The empire forestry movement spread rapidly throughout the world, and Gregory Barton's pioneering study is amongst the first to look at the origins of environmentalism in global perspective.